Multi-metal nanocluster catalyst suitable for hydrogenation reaction of naphthalene-based dinitro compound and preparation method of multi-metal nanocluster catalyst
By using a complex Cr-modified activated carbon carrier and a multi-metal catalyst of noble metals Pt, Ru, and Fe in the catalyst, the problems of low catalyst activity and poor selectivity in the hydrogenation reaction of naphthalene dinitro compounds are solved, and high efficiency and long-term operation are achieved. The catalytic effect of longevity.
Patent Information
- Application Number
- CN202411496594.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-21
AI Technical Summary
Naphthalene dinitro compounds have problems with low catalyst activity, poor selectivity and ease of inactivation in catalytic hydrogenation reactions, especially due to the lack of electrons during the conversion of nitro to amino groups and sulfur-containing substances to poison the catalyst, resulting in activity and selectivity. decline.
Complex Cr-modified activated carbon is used as a carrier to rationally design and adjust the multi-metal catalyst of precious metals Pt, Ru and non-noble metal Fe, and improve the activity and selectivity of the catalyst by enhancing the hydrogen spillover effect and the adsorption capacity of nitro functional groups.
The activity and selectivity of the catalyst are significantly improved, the service life of the catalyst is extended, poisoning and deactivation are avoided, and efficient hydrogenation reaction of naphthalene dinitro compounds is achieved.
Smart Images

Figure CN119327483A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of precious metal catalysts, and in particular relates to a multi-element metal nanocluster catalyst suitable for hydrogenation reaction of naphthalene-based dinitro compounds and a preparation method thereof. Background Art
[0002] 1,5-Diaminonaphthalene and 1,8-Diaminonaphthalene are important chemical intermediates, mainly used in the synthesis of advanced dyes, high-performance polyurethanes, photosensitive materials and specialty drugs. The traditional production method of diaminonaphthalene has the disadvantages of complex synthesis routes, large organic waste emissions and low yields; in contrast, catalytic hydrogenation is a more environmentally friendly, economical and efficient synthesis method.
[0003] In recent years, a variety of technical means have been reported to improve the activity and selectivity of aromatic nitro hydrogenation catalysts, including the use of special material carriers, multi-metal alloying, and doping with metal and non-metal elements. For example, (1,5-Dinitronaphthalene hydrogenation to 1,5-diaminonaphthalene over carbon nanotube supportednon-noble metal catalysts under mild conditions. AppliedCatalysis A-general 2016, 514, 126-134) The use of acid-modified carbon nanotubes to increase the oxygen-containing functional groups on the carrier surface for the preparation of supported nickel catalysts can effectively improve the dispersion of active metal nickel, and significantly enhance the catalytic activity of 1,5-dinitronaphthalene hydrogenation reaction, with a conversion rate of 100% and a selectivity of 92.04%. Similarly, (Nitrogen-Functionalized Active Carbon-Supported Non-Noble Nickel Nanoparticles with High Dispersity and Enhanced Catalytic Performance in Nitro Naphthalene Hydrogenation. Chemistry Select 2017, 2 (34), 11244-11249.) The catalyst prepared by researchers using nitrogen-functionalized activated carbon can effectively change the particle size and valence distribution of metallic nickel. The catalyst showed high activity, and the yield of 1,5-diaminonaphthalene was 94.75%. In addition, (Activated carbon supported bimetallic catalysts with combined catalytic effects for aromatic nitro compounds hydrogenation under mild conditions. Applied Catalysis A: General 2019, 577, 76-85.) The researchers used the strategy of metal additives to inhibit the sintering of active nickel, which increased the proportion of effective nickel on the support surface, enhanced the reducing ability, and the yield of 1,5-diaminonaphthalene reached 95.63%.
[0004] Although some progress has been made in the above research, there are still great challenges in the research of catalysts for the catalytic hydrogenation of naphthalene dinitro compounds to obtain naphthalene diamino compounds, especially in terms of low catalyst activity and poor selectivity for target products. This is due to the conversion of one nitro group (electron-withdrawing) in the raw material molecule to an amino group (electron-donating), which reduces the electron deficiency on the ring and hinders the reduction of the second nitro group; at the same time, sulfur-containing substances introduced from upstream naphthalene can poison the catalyst and significantly reduce its activity and product selectivity.
[0005] To this end, the present invention adopts complex Cr modified activated carbon as a carrier, rationally designs and adjusts the environment around the active metal Pt site, enhances the hydrogen spillover effect of the catalyst, promotes the dissociation of hydrogen and the adsorption capacity of nitro functional groups, thereby effectively improving the activity and selectivity of the catalyst and extending the service life of the catalyst. Summary of the invention
[0006] In view of the problems of reduced activity, poor selectivity, easy deactivation, etc. of the catalyst in the hydrogenation reaction of the above naphthalene dinitro compounds, the present invention provides a multi-metal nanocluster catalyst and a preparation method thereof.
[0007] To achieve the above objectives, the present invention adopts the following technical solutions.
[0008] A multi-metal nanocluster catalyst suitable for the hydrogenation reaction of naphthalene-based dinitro compounds. The catalyst is a multi-metal catalyst using a complex Cr-modified activated carbon carrier to support precious metals Pt, Ru and non-precious metal Fe.
[0009] Furthermore, the Cr element content in the multi-metal nanocluster catalyst is 0.02-0.1%, the loading amount of the precious metal Pt is 1-3%, the loading amount of Ru is 0.2-0.9%, and the loading amount of the non-precious metal Fe is 0.2-1.2%; the mass ratio of Pt, Ru and Fe is 1:0.2-0.3:0.2-0.4; the active metal particles are between 0.5-3nm, the distance between adjacent particles is less than 5nm, and the active metal particles do not form an alloy structure.
[0010] Furthermore, in the multi-metal nanocluster catalyst, the ratio of the metallic state (0 valence state) to the oxidized state (+2 and +3 valence) of Fe species is 1:2-3.
[0011] Furthermore, the preparation method of the complexed Cr modified activated carbon carrier comprises the following steps: Step 1, acid-treating the special activated carbon: weigh a certain amount of activated carbon and mix it with sulfuric acid solution; stir it in a water bath for 5-8 hours; wash and separate it, and dry it at 120°C overnight to obtain acid-treated special activated carbon; Step 2: Mix a certain mass of acid-treated special activated carbon with water, add a certain amount of chromium chloride aqueous solution to the acidified activated carbon water mixture, stir at 50° C. for 2 hours, filter, and dry at 120° C. overnight to obtain a complexed Cr-modified activated carbon carrier.
[0012] Furthermore, the adsorption capacity of special activated carbon with mesopore size between 2-3.3nm is 0-0.5cm 3 / g.nm -1 .
[0013] A method for preparing a multi-element metal nanocluster catalyst suitable for hydrogenation of naphthalene-based dinitro compounds comprises the following steps: Step 1, mixing the complex Cr modified activated carbon carrier and double distilled water in a three-necked flask, and adjusting the carbon-water mixture to a certain pH value with sodium carbonate; slowly dropping the aqueous solution of the Fe compound into the carbon-water mixture, stirring for 2 hours, filtering, washing with water, and then transferring the filter cake to a vacuum drying oven, drying, raising the temperature to a certain temperature in a reduction furnace, reducing treatment under a hydrogen atmosphere, cooling to room temperature, switching to nitrogen to replace the hydrogen in the reduction furnace, and then fully wetting the activated carbon powder with water and then taking it out to obtain the complex Cr modified activated carbon loaded with Fe species; Step 2, transfer the complexed Cr modified activated carbon loaded with Fe species into a flask, add double distilled water and stir, and pass nitrogen into the flask to obtain a mixed solution; adjust the mixed solution to a certain pH value with sodium carbonate aqueous solution, and heat it to 50°C; mix the Pt compound and the Ru compound with water, stir evenly, and obtain an impregnation solution; then drip the impregnation solution into the flask at a speed of V=50mL / h. After the dripping is completed, continue to stir for a certain time; wait until the temperature drops to room temperature, wash with water several times, and obtain a wet catalyst; put it into a vacuum drying oven for drying; Step 3, transfer the dried catalyst to a reduction furnace for reduction; after cooling to room temperature, use nitrogen to replace the hydrogen in the reduction furnace, moisten the catalyst with double distilled water, take it out and filter it, remove water until the water content of the catalyst is 60-70%, seal the reduced catalyst and place it in a cool and dry place.
[0014] Furthermore, in step 1, the mass ratio of the complexed Cr modified activated carbon carrier to the double distilled water is 1:30.
[0015] Furthermore, in step 1, the concentration of sodium carbonate is 0.25 mol / L, and the pH value of the carbon-water mixture is adjusted to 4.5-5.5.
[0016] Furthermore, in step 1, the mass concentration of the Fe compound in the aqueous solution of the Fe compound is 0.1-0.2%.
[0017] Furthermore, in step 1, drying is performed in a vacuum drying oven at 60-80° C. for 12-24 hours.
[0018] Furthermore, in step 1, the temperature of the reduction treatment is 350-450° C., and the reduction time is 2 h.
[0019] Furthermore, in step 2, the mass ratio of the complexed Cr modified activated carbon loaded with Fe species to the double distilled water is 1:20.
[0020] Furthermore, in step 2, the solubility of the sodium carbonate aqueous solution is 0.2 mol / L; and the pH value of the mixed solution is adjusted to 7-8.
[0021] Furthermore, in step 2, the mass ratio of metal Pt to Ru in the Pt compound and the Ru compound is 1:0.2-0.3.
[0022] Furthermore, in step 2, the stirring time after the addition of the impregnation liquid is completed is 6-12 hours; and nitrogen protection is maintained during the impregnation process.
[0023] Furthermore, in step 2, after multiple water washings, the catalyst is washed until the conductivity of the filtrate is 0-100 μs / cm; the vacuum drying temperature is 60-80° C., and the catalyst is dried until the water content of the catalyst is 0-6%.
[0024] Furthermore, in step 2, the Pt compound is one or a combination of platinum nitrate, platinum chloride, and chloroplatinic acid.
[0025] Furthermore, in step 2, the Ru compound is ruthenium nitrate.
[0026] Furthermore, in step 2, the Fe compound is ferrous sulfate heptahydrate or ferrous chloride.
[0027] Furthermore, in step 3, the catalyst reduction method is a hydrogen reduction method, with a heating rate of 2°C / min, a temperature of 120-150°C, and a reduction time of 6-10h.
[0028] Compared with the prior art, the present invention has the following beneficial effects.
[0029] 1. The catalyst of the present invention uses trace amounts of Cr ions to modify activated carbon, and the chromium ions are anchored to the surface of the activated carbon carrier through the interaction between the hydroxyl functional groups on the surface of the activated carbon and the chromium ions. Since the Cr ions have a d3 electronic configuration and only three d electrons in the outer layer, their empty d orbitals have strong coordination ability and a large space, and are easy to form stable complexes with toxic sulfur compounds containing lone pairs of electrons, thereby preventing these sulfur-containing compounds from being adsorbed on the active center of the catalyst, causing catalyst poisoning, effectively improving the catalyst's ability to resist sulfur poisoning, and extending the service life of the catalyst.
[0030] 2. The synergistic effect between Ru, Fe and Pt metals in the catalyst changes the environment around the Pt site, increases the dissociation rate of hydrogen, produces more active hydrogen, and strengthens the hydrogen overflow effect between metals. In addition, the highly dispersed Cr ions effectively greatly increase the dispersion of the active Pt species of the catalyst, and the metal particles are not easy to agglomerate during the reaction. Therefore, the catalyst exhibits high activity and selectivity.
[0031] 3. The catalyst of the present invention uses special activated carbon as a carrier. Due to its large effective specific surface area and special pore structure, the adsorption amount in the small mesopores of 2-3.3nm is small, which effectively reduces the diffusion resistance of the reaction and product molecules. By improving the adsorption and diffusion properties of the catalyst, it avoids the deactivation of the catalyst due to the covering of active sites by organic macromolecules such as intermediate states.
[0032] 4. The introduction of the catalyst promoter metals Ru and Fe of the present invention enhances the adsorption of the nitro group of the reactant due to the electron-rich property of the metal oxide surface, further improving the reaction rate.
[0033] 5. The catalyst of the present invention has a simple preparation process, making it suitable for industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 SEM image of the catalyst of Example 1 of the present invention.
[0035] Figure 2 HAADF diagram of the catalyst of Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The technical features of the present invention are further described below through examples, but are not limited to the examples.
[0037] A multi-metal nanocluster catalyst suitable for the hydrogenation reaction of naphthalene-based dinitro compounds. The catalyst is a multi-metal catalyst using a complex Cr-modified activated carbon carrier to support precious metals Pt, Ru and non-precious metal Fe.
[0038] Furthermore, the Cr element content in the multi-metal nanocluster catalyst is 0.02-0.1%, the loading amount of the precious metal Pt is 1-3%, the loading amount of Ru is 0.2-0.9%, and the loading amount of the non-precious metal Fe is 0.2-1.2%; the mass ratio of Pt, Ru and Fe is 1:0.2-0.3:0.2-0.4; the active metal particles are between 0.5-3nm, the distance between adjacent particles is less than 5nm, and the active metal particles do not form an alloy structure.
[0039] Furthermore, in the multi-metal nanocluster catalyst, the ratio of the metallic state (0 valence state) to the oxidized state (+2 and +3 valence) of Fe species is 1:2-3.
[0040] Furthermore, the preparation method of the complexed Cr modified activated carbon carrier comprises the following steps: Step 1, acid-treating the special activated carbon: weigh a certain amount of activated carbon and mix it with sulfuric acid solution; stir it in a water bath for 5-8 hours; wash and separate it, and dry it at 120°C overnight to obtain acid-treated special activated carbon; Step 2: Mix a certain mass of acid-treated special activated carbon with water, add a certain amount of chromium chloride aqueous solution to the acidified activated carbon water mixture, stir at 50° C. for 2 hours, filter, and dry at 120° C. overnight to obtain a complexed Cr-modified activated carbon carrier.
[0041] Furthermore, the preparation method of the complexed Cr modified activated carbon carrier comprises the following steps: Step 1, acid-treating the special activated carbon: weighing a certain amount of activated carbon and mixing it with a sulfuric acid solution with a mass concentration of 10-20% in a mass ratio of 1:10; stirring in a water bath at 50-70°C for 5-8h; washing and separating, and drying at 120°C overnight to obtain acid-treated special activated carbon; Step 2: Mix a certain mass of acid-treated special activated carbon with water, add a chromium chloride aqueous solution with a mass concentration of 0.001%-0.01% to the acidified activated carbon water mixture, stir at 50°C for 2h, filter, and dry at 120°C overnight to obtain a complexed Cr-modified activated carbon carrier.
[0042] Furthermore, the adsorption capacity of special activated carbon with mesopore size between 2-3.3nm is 0-0.5cm 3 / g.nm -1 (Analyzed using BJH model).
[0043] A method for preparing a multi-element metal nanocluster catalyst suitable for hydrogenation of naphthalene-based dinitro compounds comprises the following steps: Step 1, mixing the complex Cr modified activated carbon carrier and double distilled water in a three-necked flask, and adjusting the carbon-water mixture to a certain pH value with sodium carbonate; slowly dropping the aqueous solution of the Fe compound into the carbon-water mixture, stirring for 2 hours, filtering, washing with water, and then transferring the filter cake to a vacuum drying oven, drying, raising the temperature to a certain temperature in a reduction furnace, reducing treatment under a hydrogen atmosphere, cooling to room temperature, switching to nitrogen to replace the hydrogen in the reduction furnace, and then fully wetting the activated carbon powder with water and then taking it out to obtain the complex Cr modified activated carbon loaded with Fe species; Step 2, transfer the complexed Cr modified activated carbon loaded with Fe species into a flask, add double distilled water and stir, and pass nitrogen into the flask to obtain a mixed solution; adjust the mixed solution to a certain pH value with sodium carbonate aqueous solution, and heat it to 50°C; mix the Pt compound and the Ru compound with water, stir evenly, and obtain an impregnation solution; then drip the impregnation solution into the flask at a speed of V=50mL / h. After the dripping is completed, continue to stir for a certain time; wait until the temperature drops to room temperature, wash with water several times, and obtain a wet catalyst; put it into a vacuum drying oven for drying; Step 3, transfer the dried catalyst to a reduction furnace for reduction; after cooling to room temperature, use nitrogen to replace the hydrogen in the reduction furnace, moisten the catalyst with double distilled water, take it out and filter it, remove water until the water content of the catalyst is 60-70%, seal the reduced catalyst and place it in a cool and dry place.
[0044] Furthermore, in step 1, the mass ratio of the complexed Cr modified activated carbon carrier to the double distilled water is 1:30.
[0045] Furthermore, in step 1, the concentration of sodium carbonate is 0.25 mol / L, and the pH value of the carbon-water mixture is adjusted to 4.5-5.5.
[0046] Furthermore, in step 1, the mass concentration of the Fe compound in the aqueous solution of the Fe compound is 0.1-0.2%.
[0047] Furthermore, in step 1, drying is performed in a vacuum drying oven at 60-80° C. for 12-24 hours.
[0048] Furthermore, in step 1, the temperature of the reduction treatment is 350-450° C., and the reduction time is 2 h.
[0049] Furthermore, in step 2, the mass ratio of the complexed Cr modified activated carbon loaded with Fe species to the double distilled water is 1:20.
[0050] Furthermore, in step 2, the solubility of the sodium carbonate aqueous solution is 0.2 mol / L; and the pH value of the mixed solution is adjusted to 7-8.
[0051] Furthermore, in step 2, the mass ratio of metal Pt to Ru in the Pt compound and the Ru compound is 1:0.2-0.3.
[0052] Furthermore, in step 2, the stirring time after the addition of the impregnation liquid is completed is 6-12 hours; and nitrogen protection is maintained during the impregnation process.
[0053] Furthermore, in step 2, after multiple water washings, the catalyst is washed until the conductivity of the filtrate is 0-100 μs / cm; the vacuum drying temperature is 60-80° C., and the catalyst is dried until the water content of the catalyst is 0-6%.
[0054] Furthermore, in step 2, the Pt compound is one or a combination of platinum nitrate, platinum chloride, and chloroplatinic acid.
[0055] Furthermore, in step 2, the Ru compound is ruthenium nitrate.
[0056] Furthermore, in step 2, the Fe compound is ferrous sulfate heptahydrate or ferrous chloride.
[0057] Furthermore, in step 3, the catalyst reduction method is a hydrogen reduction method, with a heating rate of 2°C / min, a temperature of 120-150°C, and a reduction time of 6-10h.
[0058] This technology has developed a complex Cr modified activated carbon to prepare an efficient Pt-Ru-Fe multi-metal nanocluster catalyst. This catalyst has a simple preparation process, making it suitable for industrial production and application. In the hydrogenation process of dinitronaphthalene, the catalyst exhibits high activity. First, since the Cr ion has a d3 electronic configuration and only three d electrons in the outer layer, its empty d orbital has a strong coordination ability and a large space, and it is easy to form a stable complex with the S compound containing a lone pair of electrons, thereby preventing these S compounds from being adsorbed on the active center of the catalyst, causing catalyst poisoning, effectively improving the catalyst's resistance to sulfur poisoning, and extending the service life of the catalyst; secondly, the dispersion of active Pt species on the surface of the obtained catalyst is significantly improved, and the synergistic effect between Ru, Fe and Pt metals changes the environment around the Pt site. The introduction of Ru accelerates the dissociation of hydrogen, and then the dissociation of hydrogen overflows to the surface of iron oxide. The overflow effect of hydrogen between metal sites is conducive to accelerating the reaction rate of nitro hydrogenation. At the same time, Ru and Fe species, as key hydrogen overflow centers and active sites of reactants, enhance the adsorption of nitro groups due to their electron-rich characteristics; finally, the technical requirements of the catalyst of the present invention are met by selecting an activated carbon carrier with a suitable pore structure and accurately controlling the preparation process conditions of the catalyst.
[0059] Example 1.
[0060] Preparation of complex Cr modified activated carbon carrier: weigh 10g of activated carbon and mix it with a sulfuric acid solution with a mass concentration of 15% in a mass ratio of 1:10; stir in a water bath at 50°C for 8h; wash and separate, and dry at 120°C overnight to obtain acid-treated special activated carbon; mix the acid-treated special activated carbon with water, add a chromium chloride aqueous solution with a mass concentration of 0.01% to the acidified activated carbon water mixture, stir at 50°C for 2h, filter, and dry at 120°C overnight to obtain a complex Cr modified activated carbon carrier with a Cr content of 0.08wt%.
[0061] Preparation of multi-metal nanocluster catalysts suitable for hydrogenation of naphthalene dinitro compounds: Step 1: Take 1g of complex Cr modified activated carbon carrier (Cr content 0.08wt%) and mix it with 30g of secondary distilled water in a three-necked flask, use 0.25mol / L sodium carbonate to adjust the carbon-water mixture to pH 4.5, take 0.02g of ferrous sulfate heptahydrate and 10ml of water mixture (mass concentration of ferrous sulfate heptahydrate 0.2%), stir to dissolve, slowly add it dropwise to the carbon-water mixture, stir for 2h, filter, transfer the filter cake to a vacuum drying oven, dry at 60℃ for 24h, and after drying, transfer the powder to a reduction furnace and reduce it at 350℃ in a hydrogen atmosphere for 2h. After cooling to room temperature, use nitrogen to replace the hydrogen in the reduction furnace, pass secondary water to fully wet the activated carbon powder and then take it out; wherein, the ratio of the metal state (0 valence state) and the oxidation state (+2 and +3 valence) of the Fe compound is 1:3.
[0062] Step 2: Transfer the activated carbon loaded with Fe species to a flask, add 20 g of double distilled water, stir, and pass nitrogen into the flask for protection; adjust the pH value of the carbon-water mixture to 7 with 0.2 mol / L sodium carbonate aqueous solution and heat to 50°C.
[0063] Step 3: Mix 0.027g chloroplatinic acid (37.5wt%, Pt), 0.02g ruthenium nitrate (10wt%, Ru) and 15g water, stir evenly, and slowly and evenly drip into the flask at a dripping speed of V=50mL / h. After the addition is completed, continue stirring at 50°C for 6h; cool to room temperature, wash with water several times, and wash the catalyst until the conductivity of the filtrate reaches 86.3μs / cm; transfer to a vacuum drying oven for drying at 80°C for 12h, and the water content of the catalyst is 3.3%.
[0064] Step 4: The dried catalyst was transferred to a reduction furnace, hydrogen was introduced, and the catalyst was reduced at 120°C for 10 h with a heating rate of 2°C / min. After cooling to room temperature, the hydrogen in the reduction furnace was replaced with nitrogen. Secondary distilled water was introduced to moisten the catalyst, and the catalyst was taken out and filtered. The water content of the catalyst was 61.7%. The reduced catalyst was sealed and placed in a cool and dry place. The catalyst was named C1.
[0065] Example 2.
[0066] Preparation of complex Cr modified activated carbon carrier: weigh 10g of activated carbon and mix it with a 10% sulfuric acid solution in a mass ratio of 1:10; stir in a 70°C water bath for 5h; wash and separate, and dry at 120°C overnight to obtain acid-treated special activated carbon; mix the acid-treated special activated carbon with water, add a 0.005% mass concentration of chromium chloride aqueous solution to the acidified activated carbon water mixture, stir at 50°C for 2h, filter, and dry at 120°C overnight; obtain a complex Cr modified activated carbon carrier with a Cr content of 0.05wt%.
[0067] Preparation of multi-metal nanocluster catalysts suitable for hydrogenation of naphthalene dinitro compounds: Step 1: Take 1g of complex Cr modified activated carbon carrier (Cr content 0.05wt%) and mix it with 30g of secondary distilled water in a three-necked flask, use 0.25mol / L sodium carbonate to adjust the carbon-water mixture to a certain pH value of 5.5, take 0.01g of ferrous sulfate heptahydrate and 10ml of water mixture (mass concentration of ferrous sulfate heptahydrate 0.1%), stir to dissolve, slowly add it dropwise to the carbon-water mixture, stir for 2h, filter, wash with water, transfer the filter cake to a vacuum drying oven, dry at 60℃ for 24h, and after drying, transfer the powder to a reduction furnace and reduce it under a hydrogen atmosphere at 450℃ for 2h. After cooling to room temperature, use nitrogen to replace the hydrogen in the reduction furnace, pass secondary water to fully wet the activated carbon powder and then take it out; wherein, the ratio of the metal state (0 valence state) and the oxidation state (+2 and +3 valence) of the Fe compound is 1:2.1.
[0068] Step 2: Transfer the activated carbon loaded with Fe species to a flask, add 20 g of double distilled water, stir, and pass nitrogen into the flask for protection; adjust the pH value of the carbon-water mixture to 8 with 0.2 mol / L sodium carbonate aqueous solution and heat to 50°C.
[0069] Step 3: Mix 0.027g chloroplatinic acid (37.5wt%, Pt), 0.03g ruthenium nitrate (10wt%, Ru) and 15g water, stir evenly, and slowly and evenly drip into the flask at a dripping speed of V=50mL / h. After the addition is completed, continue stirring at 50°C for 12h; cool to room temperature, wash with water several times, and wash the catalyst until the conductivity of the filtrate reaches 82.9μs / cm; transfer to a vacuum drying oven for drying at 60°C for 24h, and the water content of the catalyst is 2.8%.
[0070] Step 4: The dried catalyst was transferred to a reduction furnace, hydrogen was introduced, and the catalyst was reduced at 150°C for 6 hours with a heating rate of 2°C / min. After cooling to room temperature, the hydrogen in the reduction furnace was replaced with nitrogen. Secondary distilled water was introduced to moisten the catalyst, and the catalyst was taken out and filtered. The water content of the catalyst was 65.3%. The reduced catalyst was sealed and placed in a cool and dry place. The catalyst was named C2.
[0071] Example 3.
[0072] Preparation of complex Cr modified activated carbon carrier: weigh 10g of activated carbon and mix it with a sulfuric acid solution with a mass concentration of 20% in a mass ratio of 1:10; stir in a water bath at 60°C for 6h; wash and separate, and dry at 120°C overnight to obtain acid-treated special activated carbon; mix the acid-treated special activated carbon with water, add a chromium chloride aqueous solution with a mass concentration of 0.001% to the acidified activated carbon water mixture, stir at 50°C for 2h, filter, and dry at 120°C overnight; obtain a complex Cr modified activated carbon carrier with a Cr content of 0.02wt%.
[0073] Preparation of multi-metal nanocluster catalysts suitable for hydrogenation of naphthalene dinitro compounds: Step 1: Take 1g of complex Cr modified activated carbon carrier (Cr content 0.02wt%) and mix it with 30g of secondary distilled water in a three-necked flask, use 0.25mol / L sodium carbonate to adjust the carbon-water mixture to a certain pH value of 5.0, take 0.015g of ferrous sulfate heptahydrate and 10ml of water mixture (mass concentration of ferrous sulfate heptahydrate 0.15%), stir to dissolve, slowly add it dropwise to the carbon-water mixture, stir for 2h, filter, transfer the filter cake to a vacuum drying oven, dry at 80℃ for 12h, and after drying, transfer the powder to a reduction furnace and reduce it under a hydrogen atmosphere at 400℃ for 2h. After cooling to room temperature, use nitrogen to replace the hydrogen in the reduction furnace, pass secondary water to fully wet the activated carbon powder and then take it out; wherein, the ratio of the metal state (0 valence state) to the oxidation state (+2 and +3 valence) of the Fe compound is 1:2.4.
[0074] Step 2: Transfer the activated carbon loaded with Fe species to a flask, add 20 g of double distilled water, stir, and pass nitrogen into the flask for protection; adjust the pH value of the carbon-water mixture to 7.5 with 0.2 mol / L sodium carbonate aqueous solution and heat to 50°C.
[0075] Step 3: Mix 0.027g chloroplatinic acid (37.5wt%, Pt), 0.025g ruthenium nitrate (10wt%, Ru) and 15g water, stir evenly, and slowly drip into the flask at a dripping speed of V=50mL / h. After the addition is completed, continue stirring at 50°C for 12h, cool to room temperature, wash with water several times, and wash the catalyst until the conductivity of the filtrate reaches 73.8μs / cm; transfer to a vacuum drying oven for drying at 60°C for 24h, and the water content of the catalyst is 3.1%.
[0076] Step 4: The dried catalyst was transferred to a reduction furnace, hydrogen was introduced, and the catalyst was reduced at 135°C for 8 hours with a heating rate of 2°C / min. After cooling to room temperature, the hydrogen in the reduction furnace was replaced with nitrogen. Secondary distilled water was introduced to moisten the catalyst, and the catalyst was taken out and filtered. The water content of the catalyst was 67.1%. The reduced catalyst was sealed and placed in a cool and dry place. The catalyst was named C3.
[0077] Comparative example 1.
[0078] The difference from Example 1 is that in step 1, when the activated carbon loaded with Fe species, the reduction temperature is 600° C. The ratio of the metallic state (0 valence state) to the oxidized state (+2 and +3 valence) of the Fe compound is 1:1.3, and the other conditions are the same as those in Example 1; the catalyst is named D1.
[0079] Comparative example 2.
[0080] The difference from Example 1 is that in step 1, when the activated carbon loaded with Fe species is subjected to no reduction treatment, the other conditions are the same as those in Example 1; the catalyst is named D2.
[0081] Comparative example 3.
[0082] The difference from Example 1 is that in step 2, the activated carbon loaded with Fe species is transferred to a flask, 20 g of double distilled water is added and stirred, the flask is protected by nitrogen, the pH value of the carbon-water mixture is adjusted to 6 with 0.2 mol / L sodium carbonate aqueous solution, and heated to 50°C. The other conditions are the same as in Example 1; the catalyst is named D3.
[0083] Comparative example 4.
[0084] The difference from Example 1 is that in step 2, the activated carbon loaded with Fe species is transferred to a flask, 20 g of double distilled water is added, stirred, the flask is protected by nitrogen, the pH value of the carbon-water mixture is adjusted to 9 with 0.2 mol / L sodium carbonate aqueous solution, and heated to 50°C. The other conditions are the same as in Example 1; the catalyst is named D4.
[0085] Comparative example 5.
[0086] The difference from Example 1 is that in step 3, after the active metal impregnation solution is added, the catalyst is washed until the conductivity of the filtrate reaches 308 μs / cm, and the other conditions are the same as those in Example 1; the catalyst is named D5.
[0087] Comparative Example 6.
[0088] The difference from Example 1 is that in step 4, the dried catalyst is transferred to a reduction furnace, hydrogen is introduced, and the catalyst is reduced at 250°C for 6 hours with a heating rate of 2°C / min. Other conditions are the same as in Example 1; the catalyst is named D6.
[0089] Comparative Example 7.
[0090] The difference from Example 1 is that in step 4, the dried catalyst is transferred to a reduction furnace, hydrogen is introduced, and the reduction is carried out at 90° C. for 6 h with a heating rate of 2° C. / min. Other conditions are the same as in Example 1; the catalyst is named D7.
[0091] Comparative Example 8.
[0092] The difference from Example 1 is that in step 4, the dried catalyst is reduced by wet method, and sodium borohydride is used as the reducing agent. The catalyst is mixed with 20g of water, and a mixture of 0.05g of sodium borohydride and 10ml of water is slowly added dropwise to the catalyst aqueous solution system, and stirring is continued for 1h after the addition is completed. Other conditions are the same as in Example 1; the catalyst is named D8.
[0093] Comparative Example 9.
[0094] The difference from Example 1 is that the pore size distribution of the activated carbon used in the catalyst preparation is changed, and the adsorption capacity of the mesopore size of 2-3.3 nm is 1.28 cm 3 / g.nm -1 (BJH model analysis was used), the activated carbon was not subjected to Cr modification treatment, and other conditions were the same as those in Example 1; the catalyst was named D9.
[0095] Comparative Example 10.
[0096] The difference from Example 1 is that the Fe compound (ferrous sulfate heptahydrate) is not adsorbed during the catalyst preparation process, and the catalyst preparation process from step 2 to step 4 is directly carried out using activated carbon. Other conditions are the same as in Example 1; the catalyst is named D10.
[0097] Comparative Example 11.
[0098] The difference from Example 1 is that in step 3, the catalyst is not dried after washing and filtering (water content is 69%), and is directly reduced with hydrogen. Other conditions are the same as in Example 1; the catalyst is named D11.
[0099] Comparative Example 12.
[0100] A commercial 1% Pt / C catalyst (Evonik Noblyst® P8078 1% Pt) was used and the catalyst was named D12.
[0101] Application example 1.
[0102] 5 g of 1.8-dinitronaphthalene, 30 g of toluene and 0.04 g of catalyst were put into a 250 ml high pressure reactor, and nitrogen and hydrogen were replaced three times respectively. The reaction was carried out at a temperature of 90-100 ° C, a pressure of 1.0-2.0 MPa, and a speed of 1500 r / min. The instantaneous hydrogen consumption of the reaction was monitored by a mass flow controller. When the instantaneous hydrogen consumption was 0 ml / min, the reaction was terminated.
[0103] Conversion and selectivity: The target product, by-products and raw materials were analyzed by HPLC area normalization method, and the conversion rate and selectivity were calculated.
[0104] Catalyst activity: The catalyst activity unit is mmol, calculated based on the reaction time, catalyst input and reactant consumption. sub *s -1 *g Pt -1 .
[0105] The calculation formula is: (n is the molar amount of reactant consumed, unit is mmol, t is the reaction time, unit is s, m is the mass of Pt, unit is g).
[0106] The evaluation results of the hydrogenation reduction of 1,8-dinitronaphthalene by the catalysts C1, C2 and C3 obtained in Examples 1 to 3 of the present invention are shown in Table 1.
[0107] Table 1 Catalytic hydrogenation evaluation data of Examples 1 to 3 Note: Catalyst activity unit is mmol sub *s -1 *g Pt -1 .
[0108] The evaluation results of the catalysts obtained in Comparative Examples 1 to 12 for hydrogenation reduction of 1,8-dinitronaphthalene are shown in Tables 2 to 4. Table 2 The evaluation results of the catalysts for Comparative Examples 1 to 4 are shown in the following table Note: Catalyst activity unit is mmol sub *s -1 *g Pt -1 .
[0109] Table 3 The evaluation results of the catalysts for Comparative Examples 5 to 8 are shown in the following table Note: Catalyst activity unit is mmol sub *s -1 *g Pt -1 .
[0110] Table 4 The evaluation results of the catalysts for Comparative Examples 9 to 12 are shown in the following table Note: Catalyst activity unit is mmol sub *s -1 *g Pt -1 .
[0111] As can be seen from Table 1, for the application of 1,8-dinitronaphthalene hydrogenation to 1,8-diaminonaphthalene, the catalyst of the present invention can be used 8 times and has high activity and selectivity. After 8 times of use, the conversion rate still reaches 100%, the selectivity remains above 98.6%, and the activity is higher than 22.7 mmol sub *s -1 *g Pt -1 The catalysts prepared under other conditions (Comparative Examples 1 to 11) and the commercial Pt / C catalyst (Comparative Example 12) had low activity and short service life, low activity during application, and fast deactivation rate. The conversion rate did not reach 100% in the second application, and the activity was less than 10 mmol after 4 applications. sub *s -1 *g Pt -1 The conversion rate is as low as 90.5%, and the selectivity is as low as 92.9%. That is, the catalyst prepared outside the technical rights of the present invention has a short service life and poor stability. The second application activity of the commercial Pt / C catalyst is only 6.1mmol sub *s -1 *g Pt -1 The above results fully demonstrate that the catalyst of the present invention has the characteristics of high activity, high selectivity and long life in the hydrogenation reaction of 1,8-dinitronaphthalene.
[0112] Application example 2.
[0113] 5 g of 1.5-dinitronaphthalene, 30 g of toluene and 0.04 g of catalyst were put into a 250 ml high pressure reactor, and nitrogen and hydrogen were replaced three times respectively. The reaction was carried out at a temperature of 90-100° C., a pressure of 1.0-2.0 MPa, and a rotation speed of 1500 r / min. The instantaneous hydrogen consumption of the reaction was monitored by a mass flow controller. When the instantaneous hydrogen consumption was 0 ml / min, the reaction was terminated.
[0114] Conversion and selectivity: The target product, by-products and raw materials were analyzed by HPLC area normalization method, and the conversion rate and selectivity were calculated.
[0115] Catalyst activity: The catalyst activity unit is mmol, calculated based on the reaction time, catalyst input and reactant consumption. sub *s -1 *g Pt -1 .
[0116] The calculation formula is: (n is the molar amount of reactant consumed, unit is mmol, t is the reaction time, unit is s, m is the mass of Pt, unit is g).
[0117] The evaluation results of the hydrogenation reduction of 1,5-dinitronaphthalene by the catalysts C1, C2 and C3 obtained in Examples 1 to 3 of the present invention are shown in Table 5.
[0118] Table 5 Catalytic hydrogenation evaluation data of Examples 1 to 3 Note: Catalyst activity unit is mmol sub *s -1 *g Pt -1 .
[0119] The evaluation results of the hydrogenation reduction of 1,5-dinitronaphthalene using the catalysts obtained in Comparative Examples 1 to 12 are shown in Tables 6 to 8 respectively.
[0120] Table 6 The evaluation results of the catalysts for Comparative Examples 1 to 4 are shown in the following table Note: Catalyst activity unit is mmol sub *s -1 *g Pt -1 .
[0121] Table 7 The evaluation results of the catalysts for Comparative Examples 5 to 8 are shown in the following table Note: Catalyst activity unit is mmol sub *s -1 *g Pt -1 .
[0122] Table 8 The evaluation results of the catalysts for Comparative Examples 9 to 12 are shown in the following table Note: Catalyst activity unit is mmol sub *s -1 *g Pt -1 As can be seen from Table 5, for the application of 1.5-dinitronaphthalene hydrogenation to 1.5-diaminonaphthalene, the catalyst of the present invention can be applied 9 times and maintains high activity and selectivity. The conversion rate after 9 applications still reaches 100%, the selectivity remains above 98.7%, and the activity is higher than 25.4mmol sub *s -1 *g Pt -1 The catalysts prepared under other conditions (Comparative Examples 1 to 11) and the commercial Pt / C catalyst (Comparative Example 12) had low activity and short service life. The catalyst deactivated quickly during the application process. The conversion rate did not reach 100% in the second application. After 5 applications, the activity was less than 10 mmol. sub *s -1 *g Pt -1 The conversion rate is as low as 92.4%, and the selectivity is as low as 90.2%. That is, the catalyst prepared outside the technical rights of the present invention has a short service life, low activity and poor selectivity. The second-time activity of the ordinary commercial Pt / C catalyst is only 6.6mmol sub *s -1 *g Pt -1 The above results fully demonstrate that the catalyst of the present invention has the characteristics of high activity and high selectivity in the hydrogenation reaction of 1.5-dinitronaphthalene.
[0123] In summary, through the evaluation data of Application Examples 1 and 2, it can be seen that the technology selects activated carbon carriers with suitable pore structures, carries out complex Cr modification, and develops efficient Pt-Ru-Fe ternary metal nanocluster catalysts by precisely controlling the preparation process conditions of the catalyst. The catalysts show high activity in the hydrogenation process of 1.8 / 1.5-dinitronaphthalene. Firstly, since the Cr ion has a d3 electronic configuration and has only three d electrons in the outer layer, its empty d orbital has a strong coordination ability and a large space, and it is easy to form a stable complex with the S compound containing a lone pair of electrons, thereby preventing these S compounds from being adsorbed on the active center of the catalyst, causing catalyst poisoning, effectively improving the catalyst's ability to resist sulfur poisoning, and extending the service life of the catalyst; secondly, the highly dispersed Cr ion effectively greatly improves the dispersion of the active Pt species of the catalyst, and the metal particles are not easy to agglomerate during the reaction. In addition, the synergistic effect between Ru, Fe and Pt metals changes the environment around the Pt site. The introduction of Ru accelerates the dissociation of hydrogen, and then the dissociation of hydrogen overflows to the surface of iron oxide. The overflow effect of hydrogen between metal sites is conducive to accelerating the reaction rate of nitro hydrogenation. At the same time, Ru and Fe species, as key hydrogen overflow centers and active sites of reactants, enhance the adsorption of nitro groups due to their electron-rich characteristics, and further improve the reaction rate; finally, the technology of the present invention has the advantages of simple preparation process and suitability for industrial production and application.
Claims
1. A multi-metal nanocluster catalyst suitable for hydrogenation of naphthalene dinitro compounds, characterized in that: The catalyst is a multi-metal catalyst using a complex Cr-modified activated carbon carrier to support precious metals Pt, Ru and non-precious metal Fe; The Cr element content in the multi-metal nanocluster catalyst is 0.02-0.1%, the loading amount of the precious metal Pt is 1-3%, the loading amount of Ru is 0.2-0.9%, and the loading amount of the non-precious metal Fe is 0.2-1.2%; the mass ratio of Pt, Ru and Fe is 1:0.2-0.3:0.2-0.4; the active metal particles are between 0.5-3nm, the distance between adjacent particles is less than 5nm, and the active metal particles do not form an alloy structure.
2. The multi-metal nanocluster catalyst according to claim 1, characterized in that: In multi-metal nanocluster catalysts, the ratio of metallic state to oxidation state of Fe species is 1:2-3.
3. The multi-metal nanocluster catalyst according to claim 1, characterized in that: The preparation method of the complexed Cr modified activated carbon carrier comprises the following steps: Step 1, acid-treating the special activated carbon: weigh a certain amount of activated carbon and mix it with sulfuric acid solution; stir it in a water bath for 5-8 hours; wash and separate it, and dry it at 120°C overnight to obtain acid-treated special activated carbon; Step 2: Mix a certain mass of acid-treated special activated carbon with water, add a certain amount of chromium chloride aqueous solution to the acidified activated carbon water mixture, stir at 50° C. for 2 hours, filter, and dry at 120° C. overnight to obtain a complexed Cr-modified activated carbon carrier.
4. The multi-metal nanocluster catalyst according to claim 3, characterized in that: The mesopore size of special activated carbon is between 2-3.3nm and the adsorption capacity is 0-0.5cm 3 / g.nm -1 .
5. A method for preparing a multi-metal nanocluster catalyst suitable for hydrogenation of naphthalene dinitro compounds, characterized in that: The steps include: Step 1, mixing the complex Cr modified activated carbon carrier and double distilled water in a three-necked flask, and adjusting the carbon-water mixture to a certain pH value with sodium carbonate; slowly dropping the aqueous solution of the Fe compound into the carbon-water mixture, stirring for 2 hours, filtering, washing with water, and then transferring the filter cake to a vacuum drying oven, drying, raising the temperature to a certain temperature in a reduction furnace, reducing treatment under a hydrogen atmosphere, cooling to room temperature, switching to nitrogen to replace the hydrogen in the reduction furnace, and then fully wetting the activated carbon powder with water and then taking it out to obtain the complex Cr modified activated carbon loaded with Fe species; Step 2, transfer the complexed Cr modified activated carbon loaded with Fe species into a flask, add double distilled water and stir, and pass nitrogen into the flask to obtain a mixed solution; adjust the mixed solution to a certain pH value with sodium carbonate aqueous solution, and heat it to 50°C; mix the Pt compound and the Ru compound with water, stir evenly, and obtain an impregnation solution; then drip the impregnation solution into the flask at a speed of V=50mL / h. After the dripping is completed, continue to stir for a certain time; wait until the temperature drops to room temperature, wash with water several times, and obtain a wet catalyst; put it into a vacuum drying oven for drying; Step 3, transfer the dried catalyst to a reduction furnace for reduction; after cooling to room temperature, use nitrogen to replace the hydrogen in the reduction furnace, moisten the catalyst with double distilled water, take it out and filter it, remove water until the water content of the catalyst is 60-70%, seal the reduced catalyst and place it in a cool and dry place.
6. The preparation method according to claim 5, characterized in that: In the step 1, the mass ratio of the complexed Cr modified activated carbon carrier to the secondary distilled water is 1:30; the sodium carbonate concentration is 0.25 mol / L, and the pH value of the carbon-water mixture is adjusted to 4.5-5.5; the mass concentration of the Fe compound in the aqueous solution is 0.1-0.2%; the mixture is dried at 60-80° C. in a vacuum drying oven for 12-24 hours; the reduction treatment temperature is 350-450° C., and the reduction time is 2 hours.
7. The preparation method according to claim 5, characterized in that: In the step 2, the mass ratio of the complexed Cr modified activated carbon loaded with Fe species to the double distilled water is 1:20; the solubility of the sodium carbonate aqueous solution is 0.2 mol / L; the pH value of the mixed solution is adjusted to 7-8; the mass ratio of metal Pt and Ru in the Pt compound and the Ru compound is 1:0.2-0.
3.
8. The preparation method according to claim 5, characterized in that: In the step 2, the stirring time after the impregnation liquid is added is 6-12 hours; the nitrogen protection is maintained during the impregnation process; after multiple water washings, the catalyst is washed until the conductivity of the filtrate is 0-100 μs / cm; the vacuum drying temperature is 60-80° C., and the catalyst is dried until the water content of the catalyst is 0-6%.
9. The preparation method according to claim 5, characterized in that: In step 2, the Pt compound is one or a combination of platinum nitrate, platinum chloride, and chloroplatinic acid; the Ru compound is ruthenium nitrate; and the Fe compound is ferrous sulfate heptahydrate or ferrous chloride.
10. The preparation method according to claim 5, characterized in that: In step 3, the catalyst reduction method is hydrogen reduction method, the heating rate is 2°C / min, the temperature is 120-150°C, and the reduction time is 6-10h.